Primary versus secondary headache in children: a frequent diagnostic challenge in clinical routine - Roser, Timo; Bonfert, Michaela; Ebinger, Friedrich; Blankenburg, Markus; Ertl-Wagner, Birgit; Heinen, Florian (Neuropediatrics, 2013)
A sensitive and specific triage of patients with primary or secondary headache is a major concern in evaluating pediatric headache patients. History and physical examination are the major tools for differentiating primary headache disorders from symptomatic headaches caused by defined pathologies. If the criteria of the International Headache Society for a primary headache disorder are met, no further investigations are necessary. However, physicians should be familiar with subtle signs in history and physical examination that raise suspicion of intracranial pathology. These features, also named “red flags” and “relatively red flags,” are outlined in detail in this review. Any red flag should prompt neuroimaging. In case of relatively red flags, a more restrained approach can be appropriate depending on the individual setting. Excessive concerns of patients and parents regarding an underlying pathology can constitute an indication for neuroimaging. Offering neuroimaging implicates the important issues of incidental findings and of “false reassurance.” These risks should be discussed with patients and parents before the investigation. In any pediatric headache patient, regular clinical reevaluations should be warranted, even if neuroimaging is normal. The value of clinical follow-up examinations for a reasonable and reliable assessment of the patients cannot be overestimated.
Gesehen am 20.01.2022